Aliénation et réinvention dans l'œuvre de Jamaica Kincaid - Yassine-Diab, Nadia (Horizons anglophones, 2014)
Caribbean literature maintains a dual relationship with the culture of the former colonizers, hesitating between resistance and imitation, deterritorialization and reterritorialization, alienation and reinvention. Jamaica Kincaid's connection with her literary and historical heritage is a dynamic one. Her writing is postcolonial in the political more than the historical sense. Like Kincaid herself, the characters explore the boundaries between filiation and affiliation, adopting strategies of reappropriation to respond to their alienation in their relationships with their mothers. Their reclaiming of their bodies leads to self-reinvention, and to the reappropriation of history and space. Kincaid herself searches for an artistic space in which to reinvent herself. She combines photography, painting, and gardening with writing, adopting different strategies for reappropriating and decolonizing language. She writes in the oppressor's tongue and subverts it, combining different voices in the space of her texts.